THE INFLUENCE OF THE EDUCATION OF THE TA'LIMUL QUR'AN ASSEMBLY IN THE FORMATION OF CHILDREN'S CHARACTER IN SENURO VILLAGE - Jannah, Roudhotul; Helmi, Henny; Husain, Azizah (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This research aims to examine the influence of education at Majelis Ta'limul Qur'an on the character building of children in Senuro Village, with a special focus on the learning materials delivered in instilling moral and religious values in children. This research uses a descriptive qualitative approach, using purvosiv random samlping techniques, with data collection techniques in the form of interviews, observation, and documentation. The results of the study show that the learning materials at Majelis Ta'limul Qur'an are delivered through interactive methods and in accordance with the development of children's age, such as dialog, storytelling, exemplary, targhib and tarhib and habituation. The material effectively instills character values in children. Children who participated in the assembly activities experienced an increase in positive attitudes, such as discipline, better morals, and increased responsibility. Parents also feel the positive impact of the learning materials provided, seen from changes in children's behavior at home and the surrounding environment. Thus, education at Majelis Ta'limul Qur'an not only improves children's religious abilities but also becomes a fortress in shaping character in accordance with Islamic values amid the challenges of the times